Influence of socio-demographic factors on coverage of full vaccination among children aged 12-23 months: a study in Indian context (2015-2016) - Tarikul Islam; Salim Mandal; Pradip Chouhan (Taylor & Francis Group, 2021)
Background Vaccine-preventable diseases (VPDs) are one of the key public health concerns in low and middle-income countries due to incomplete vaccination coverage. Nearly three million children up to 5 years of age die due to VPDs each year. Vaccination plays a significant role in reducing child mortality and morbidity from VPDs. Globally, full vaccination coverage efficiently saves two to three million children's lives from life-threatening VPDs. Objective This study intends to inspect the influence of socio-demographic factors on full vaccination coverage of children aged 12-23 months in India. Methods A cross-sectional observational study was carried out using the NFHS-4, 2015-2016 data of India. A total of 44,771 children aged 12-23 months born to the mothers aged 15-49 years in the last 5 years preceding the survey were used for this study. For the analyses of the data, Bivariate and Multivariate analyses were performed. Results The prevalence of full vaccination coverage of children aged 12-23 months in India was 62%. The result of the study indicated that maternal educational attainment, household wealth status, child size at birth, and maternal health-care services are the main significant predictors of full vaccination coverage. Other socio-demographic factors include maternal age, sex of the household head, exposure to mass media, child birth order, social category, religion, place of residence and region also play significant role in the coverage of full vaccination. Conclusion The study found that socio-demographic factors play a significant role in full vaccination coverage children in India. Therefore, policymaker and administrators should accentuate the inventive approach for the development of women education, improvement of family income, and easy accessibility of maternal and child healthcare services to surmount the impediment of children full vaccination coverage, which eventually reduce the risk of child morbidity and mortality.